Weavers of dreams, unite! : actor's unionism in early twentieth-century America - Holmes, Sean P. (University of Illinois Press, 2013)
Published to coincide with the centenary of the founding of the Actors' Equity Association in 1913, 'Weavers of Dreams, Unite!' explores the history of actors' unionism in the United States from the late 19th century to the onset of the Great Depression. Drawing upon hitherto untapped archival resources in New York & Los Angeles, Sean P. Holmes documents how American stage actors used trade unionism to construct for themselves an occupational identity that foregrounded both their artistry & their respectability.